THE ORIGIN OF ORGANIC MATTER IN THE SOLAR SYSTEM: EVIDENCE FROM THE INTERPLANETARY DUST PARTICLES - Flynn G.J.; Keller L.P.; Feser M.; Wirick S.; Jacobsen C. (My University, 2003)
The detailed examination of meteorites and interplanetary dust particles provides an opportunity to infer the origin of the organic matter found in primitive Solar System materials. If this organic matter were produced by aqueous alteration of elemental (graphitic or amorphous) carbon on an asteroid, then we would expect to see the organic matter occurring preferentially in interplanetary materials that exhibit evidence of aqueous activity, such as the presence of hydrated silicates. On the other hand, if the organic matter were produced either during the nebula phase of Solar System evolution or in the interstellar medium, we might expect this organic matter to be incorporated into the dust as it formed. In that case pre-biotic organic matter would be present in both the anhydrous and the hydrated interplanetary materials. We have performed carbon X-ray absorption near-edge structure spectroscopy and infrared spectroscopy on primitive anhydrous and hydrated interplanetary dust particles (IDPs) collected by NASA from the Earth's stratosphere. We find that organic matter is present in similar types and abundances in both the anhydrous and the hydrated IDPs, and, in the anhydrous IDPs some of this organic matter is the ''glue'' that holds grains together. These measurements provide the first direct, experimental evidence from the comparison of extraterrestrial samples that the bulk of the pre-biotic organic matter occurs in similar types and abundances in both hydrated and anhydrous samples. This indicates that the bulk of the pre-biotic organic matter in the Solar System did not form by aqueous processing, but, instead, had already formed at the time that primitive, anhydrous dust was being assembled. Thus, the bulk of the pre-biotic organic matter in the Solar System was formed by non-aqueous processing, occurring in either the Solar nebula or in an interstellar environment. Aqueous processing on asteroids may have altered this pre-existing organic matter, but such processing did not affect in any substantial way the C=O content of the organic matter, the aliphatic C-H abundance, or the mean aliphatic chain length.